Aspergillus species contamination in concentrate feeds collected from specialized dairy farms and local markets in selected urban centers of eastern Ethiopia - Tesfaye, Angassa; Mohammed, Abdi; Yusuf, Mohammed; Yusuf, Yesihak (Frontiers in Sustainable Food Systems, 2024)
This study aimed to identify and examine the prevalence of Aspergillus species in three types of feed collected from specialized dairy farms and local markets in Chiro town, Dire Dawa, and Harar cities in eastern Ethiopia. A total of 180 dairy feed samples were collected and sown, initially on YES agar and then sub-cultured to AFPA to identify Aspergillus species based on colony color, conidia, vesicle, and phialide features. Additionally, the aflatoxigenic potential of the colonies was tested using CAM-based UV fluorescence. The study revealed that the prevalence of Aspergillus species was 80.6% in dairy feeds with a mean count of 3.04 log10cfu/g. Among the identified species, A. flavus was found to be highly prevalent (80%) in the feed with a mean of 2.73 log10cfu/g (7.45 × 103 cfu/g). Meanwhile, A. parasiticus and A. niger were observed in 73.3% (mean 2.43 log10cfu/g) and 58.3% (mean 1.68 log10cfu/g) of feeds, respectively. Furthermore, the prevalence rates of all Aspergillus species in feeds were not significant (p > 0.05) among the study sites and feed sources. However, the mean count of total Aspergillus (3.47 ± 1.34 log10cfu/g), A. flavus (3.20 ± 1.27 log10cfu/g), and A. parasiticus (2.82 ± 1.41 log10cfu/g) was significantly higher in feeds from Dire Dawa city. Additionally, both the prevalence rates and mean counts of total Aspergillus (37.9% and 3.65 ± 1.16 log10cfu/g), A. flavus (38.2% and 3.26 ± 1.12 log10cfu/g), A. parasiticus (38.6% and 2.98 ± 1.34 log10cfu/g), and A. niger (37.1% and 2.11 ± 1.57 log10cfu/g) in total mixed ration were significantly higher (p < 0.05) than in other feed types. Out of the screened Aspergillus colonies, 81.42% were found to be aflatoxigenic, with 58.32% belonging to A. flavus and 41.68% to A. parasiticus. Therefore, widespread contamination of Aspergillus species in dairy feeds across the study sites raises food safety and public health concerns, which highlights the urgent need for stringent measures in feed quality control to curb its prevalence and the risk of aflatoxin exposure.